The Use Of The SAMR Model To Improve Students Speaking Ability - Saffa Aulia Lestari; Ahmad Munir (Universitas Negeri Semarang, 2022)
Speaking is a God-given human ability to communicate with one another using voices and language that other humans can recognize. The education team hopes that students will be able to employ and master speaking strategies as a result of teaching and learning activities both inside and outside the classroom using the Technology SAMR (Substitution, Augmentation, Modification, Redefinition) Model. The study aims to determine whether there is a significant difference in student’s ability to speak English when using the SAMR Model compared to when using the Manual Model and also to learn about the experiences students have while learning to use the SAMR Model. This study conducts quasi-experimental research in order to collect significant improvement data on the use of the SAMR model to improve students' ability to speak procedure text. Taking the results of the pre-test and post-test scores on the type of presentation test and showing a high level of agreement between researchers and observers, the t-test and ANCOVA test showed a significant change in student learning outcomes, indicating that the SAMR Model follows the requested process and has an impact on student learning.